The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.21093/ijeltal.v7i1.1193
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Back-translation Instruction with Collaborative Activities on Iranian English Students’ Translation Achievement

Abstract: The present quasi-experimental study with a non-equivalent control group pretest-posttest design investigated the impact of back-translation teaching with collaborative activities on Iranian English translation students’ translation achievement. To this end, 30Iranian EFL translation students studying at Islamic Azad University North Tehran Branch were nominated based on convenience sampling. The Oxford Placement Test (OPT) and a translation pretest were directed to inspect the contributors’ homogeneity prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Needless to say, practice-oriented translation education is an urgent need in the field of translation. Studies showed that those students experienced teacher-student cooperation in class setting achieved more than others (Beiki et al,2020 a;Mohammadi et al, 2022;Sanders & Horn, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Needless to say, practice-oriented translation education is an urgent need in the field of translation. Studies showed that those students experienced teacher-student cooperation in class setting achieved more than others (Beiki et al,2020 a;Mohammadi et al, 2022;Sanders & Horn, 1998).…”
Section: Introductionmentioning
confidence: 99%